Estratégia robusta para a gestão de drenagem urbana em cenário de mudança do clima - Sabóia, Marcos Abílio Medeiros de (2016)
The changes observed in extreme weather events reflect the influence of Climatic changes due to anthropogenic factors, besides the variability Climate. According to future climate projections, the increase in average Of the terrestrial surface, will cause strong changes in the average annual precipitation of Almost the entire planet. The present work aims to evaluate the impact of the possible scenarios Climate change in urban drainage systems, in addition, Implementation costs of these systems based on the various scenarios of Climatic conditions studied and proposed a robust solution to the problem of optimization of Costs. The specific location of the study will be one of the sub-basins of Rio Cocó, in the city of Fortaleza-CE. Precipitation data from six models of Circulation, they are: bcc-csm1, CanESM2, CCSM4, CESM1-CAM5, inmcm4 and MIROC5. These data were extracted and interpolated to the city of Fortaleza-CE. This information was used to generate new projected IDF equations For the future through the use of the "Quantis Correspondence Method Equidistant ", based on the climate projections RCP 4,5 and RCP 8.5. The new values Precipitation generated by these new IDF curves were used as one of the data Of the HEC-HMS program, which is a software capable of calculating the flow and Volume drained in a given basin. The results showed that Large increases in flows and volumes drained in the analyzed drainage system, And the RCP 8.5 scenario presented even more marked values ​​than the one generated By the RCP scenario 4.5.